السِّیَاسَةُ السَّكَنِیَةُ فِي الجَزَائِر 2015- دِرَاسَةُ تَقیِمِیَةُ 2004 - قشاشطة, أبوبكر (My University, 2015)
و بالرجوع إلى ما تم التطرق إلیه فإن مؤش ا رت الفرضیات تحققت( تم إثبات "فشل السیاسة السكنیة في القضاء على أزمة السكن- الفرضیة 1"، و نفي الفرضیة 2 التي تنص على " نجاح السیاسة السكنیة یتوقف على الوعود الحكومیة" بل على تداركها للخل في هذه السیاسات )، إلا أنه یبقى عامل النسبیة في صحة هذه الفرضیات، وهذا طبیعي لأن د ا رستنا لهذا الموضوع لا تعدوا أن تكون في الحقیقة إلا محاولة متواضعة للبحث عن مدى نجاح السیاسات التي تتبعها الدولة في إدارتها لأزمة السكن، وهذا من خلال توظیف و إستخدام المعلومات و المعطیات المتوفرة، ولذلك فإن هذه الد ا رسة لا یمكن أن تلم بكل ز وایا هذا الموضوع لأنه في الحقیقة موضوع واسع النطاق، و علیه فإننا یمكن أن نقدم بعض المقترحات و التوصیات التي نسعى من خلالها تقدیم مساهمتنا في الحد من أزمة السكنAnd with reference to what was discussed, the hypothesis indicators have been achieved (the policy failure has been proven). housing in eliminating the housing crisis - Hypothesis 1", and denying Hypothesis 2 which states "Success The housing policy depends on the government's promises, "rather on its rectification of the defects in these policies" except It remains the relativity factor in the validity of these hypotheses, and this is natural because our study of this subject does not It is, in fact, only a modest attempt to research the success of its policies The state in its management of the housing crisis, and this is through the employment and use of information and data available, and therefore this study cannot cover all angles of this topic because in fact It is a wide-ranging topic, and accordingly we can present some suggestions and recommendations that we seek Through which we make our contribution to reducing the housing crisis
م.س.ع 15
Keywords: ازمة -السكن; And with reference to what was discussed, the hypothesis indicators have been achieved (the policy failure has been proven). housing in eliminating the housing crisis - Hypothesis 1", and denying Hypothesis 2 which states "Success The housing policy depends on the government's promises, "rather on its rectification of the defects in these policies" except It remains the relativity factor in the validity of these hypotheses, and this is natural because our study of this subject does not It is, in fact, only a modest attempt to research the success of its policies The state in its management of the housing crisis, and this is through the employment and use of information and data available, and therefore this study cannot cover all angles of this topic because in fact It is a wide-ranging topic, and accordingly we can present some suggestions and recommendations that we seek Through which we make our contribution to reducing the housing crisis